2002
DOI: 10.2169/internalmedicine.41.813
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 and MIP-1A Gene Polymorphisms in Japanese Patients with Sarcoidosis.

Abstract: Objectives Monocyte chemoattractant protein (MCP)-1 and macrophage inflammatory protein (MIP)-loc exhibit chemotactic activity toward macrophages/monocytes and induce the production of inflammatory cytokines affecting granuloma formation. Recently, a single nucleotide polymorphism (SNP) in the MCP-1 distal regulatory region and a dinucleotide repeat in the MIP-1Agene promoter region were identified. Weinvestigated the relationships between the polymorphisms and susceptibility to sarcoidosis, clinical manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
(25 reference statements)
3
6
0
Order By: Relevance
“…In the present study, the gene polymorphism of MCP‐1 was analyzed. The genotype and allele frequencies were similar to those of previously reported studies in healthy Chinese subjects (16,17), and those in Japanese (18) and Korean (19) subjects. The genotype and allele frequencies in Chinese subjects were obviously different from those of African–American, Caucasian and Hispanic subjects (11,12,20); the G‐allele frequency was increased in Chinese subjects.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the gene polymorphism of MCP‐1 was analyzed. The genotype and allele frequencies were similar to those of previously reported studies in healthy Chinese subjects (16,17), and those in Japanese (18) and Korean (19) subjects. The genotype and allele frequencies in Chinese subjects were obviously different from those of African–American, Caucasian and Hispanic subjects (11,12,20); the G‐allele frequency was increased in Chinese subjects.…”
Section: Discussionsupporting
confidence: 88%
“…A multivariate linear regression analysis was performed to (27%) 10 ; however, it is quite different to that reported in the Korean population (60%) 22 and Japanese population (71%). 23 In our study population, the MCP-1 -2518G allele was observed to be associated with higher MCP-1 levels as previously observed. 10,23, 24 We did not, however, observe any correlation between MCP-1 levels and metabolic syndrome or its individual components.…”
Section: Discussionsupporting
confidence: 87%
“…DNA was isolated from the whole blood and genotyping of FCGR2A p.R131H (rs1801274) and CCL2 c.-2518 A > G (rs1024611) polymorphisms were investigated using a PCR-restriction fragment length based polymorphism method as described earlier [11,12].…”
Section: Genotyping Methodsmentioning
confidence: 99%